Trilha sonora em jogos digitais: uma análise histórica, funcional e suas relações com a música no cinema - Marcos de Lima e Mello (2018)
This dissertation proposes to investigate the main characteristics of the soundtrack of digital games. It presents an analysis of its historical evolution, its most influential composers, as well as its functional evolution. Some important points concerning its role in the aid of interaction, immersion and narrative are also detailed. This initial information is the base for the subsequent research, which seeks to establish a comparison between the soundtrack of digital games and cinema, pointing out common characteristics, as well as their specificities